Enhancing geographic coordinates representation standard for reverse geocoding web services - Al-Habshi, Mohammed Mustafa Abdulrahman (2018)
Reverse-geocoding is Location Base Services (LBS) that supports mobile and web applications. Using a given geographical coordinates, it provides human-readable addresses and other related information. These days, regardless of Geographic Information System (GIS) and Spatial Data Infrastructure (SDI), reverse-geocoding web services provide the backbone of many of web, mobile, and Internet-of-Things (IoT) applications. These developments in Information and Communication Technologies (ICT) founded standardization diversity, where differences between web services providers and organizations committees, such International Standardization Organization (ISO) and Open Geospatial Consortium (OGC). This research interest in ISO6709 “standard representation of geographic point”. The standard provides guidelines in term of geographic point location representation. While its main concern in having a constancy in data exchange, it lacks providing the basis of decimal degrees digits precision quality measurement. The digit precision has been mentioned in the ISO6709, but the basis of geospatial precision was not mentioned. In addition, the standard doesn’t provide guidelines related impact of precision quality on data storage and internet bandwidth, where the majority of coordinates’ format is text. Therefore, further effective standardization is in need. The research approach to tackle the precision quality of decimal degrees by utilizing European Petroleum Survey Group (EPSG) dataset of Coordinate Reference System and use it to identify the effect of rounding decimal digits in a metric measurement. The research developed a standardized Intuitive Geospatial Relational Query Model (IGRQM) that can be used to determine latest unique Coordinate Reference System (CRS) for a single geographic point. The IGRQM contains of 3341 spatial features with 6526 CRS and was used within a geospatial query process and tested against 100 generated and distributed geographic points with addresses around the globe, where the decimal digits are between 10 and 14. The development process was exploration research to discover patterns of non-unique CRS through qualitative analysis and embed them as rules of CRS exclusions in the IGRQM. The results were each of the 100 generated points have a single latest metric unique CRS, where the distinctive count of CRS is 93. The 100 points with their CRS were used to measure the impact of decimal digits rounding on metric distance. These measurements summary was validated with World Geodetic System (WGS) 1984 spheroid results. Although the difference doesn’t show high variation, the research findings provided an evidence and a method that respect and consider counties developed CRS. In addition, a simple table as guidelines was developed to show the bytes size of the decimal digit in scaling. Benchmarking the guidelines found the data is maintained within about 68% ± 1% of the original size without any algorithm compression. This study provides some basis for consideration when addressing geographic standards rather arbitrary.